An enzyme cascade fluorescence-based assay for the quantification of phenylalanine in serum. Issue 4 (21st January 2022) - Meng, Leilei; Hu, Rui; Chen, Jinping; Yu, Tianjun; Cai, Xiaopin; Yang, Guoqiang; Zeng, Yi; Li, Yi
Abstract : An enzyme cascade fluorescence assay for phenylalanine quantification was established by the combination of phenylalanine dehydrogenase and nitroreductase. Abstract : The quantification of phenylalanine in clinical samples is essential for the diagnosis and treatment of neonatal phenylketonuria. In this report, an enzyme cascade strategy was proposed and a high-efficiency fluorescence assay was established for rapid and convenient phenylalanine quantification. The assay involves phenylalanine dehydrogenase for the quantitative metabolization of phenylalanine and the formation of NADH, as well as nitroreductase combining a nitroaromatic substrate for the fluorescent quantification of NADH and subsequently phenylalanine. The phenylalanine levels in clinical serum determined by this fluorescence assay are consistent with those from HPLC. This straightforward approach provides a versatile strategy for the development of cost-effective and convenient assays for mass screening and metabolite monitoring.